Base of the Measles Virus Fusion Trimer Head Receives the Signal That Triggers Membrane Fusion - Apte-Sengupta, Swapna (American Society for Biochemistry and Molecular Biology, 2012)
The measles virus (MV) fusion (F) protein trimer executes membrane fusion after receiving a signal elicited by receptor binding to the hemagglutinin (H) tetramer. Where and how this signal is received is understood neither for MV nor for other paramyxoviruses. Because only the prefusion structure of the parainfluenza virus 5 (PIV5) F-trimer is available, to study signal receipt by the MV F-trimer, we generated and energy-refined a homology model. We used two approaches to predict surface residues of the model interacting with other proteins. Both approaches measured interface propensity values for patches of residues. The second approach identified, in addition, individual residues based on the conservation of physical chemical properties among F-proteins. Altogether, about 50 candidate interactive residues were identified. Through iterative cycles of mutagenesis and functional analysis, we characterized six residues that are required specifically for signal transmission; their mutation interferes with fusion, although still allowing efficient F-protein processing and cell surface transport. One residue is located adjacent to the fusion peptide, four line a cavity in the base of the F-trimer head, while the sixth residue is located near this cavity. Hydrophobic interactions in the cavity sustain the fusion process and contacts with H. The cavity is flanked by two different subunits of the F-trimer. Tetrameric H-stalks may be lodged in apposed cavities of two F-trimers. Because these insights are based on a PIV5 homology model, the signal receipt mechanism may be conserved among paramyxoviruses.